Sociodemographic characteristics of persons committing suicide in Durban, South Africa: 2006-2007 - Soornarain S. Naidoo; Lourens Schlebusch (AOSIS, 2014)
Background: Suicidal behaviour is a leading contributor to the burden of disease worldwide and varies widely between countries. South African figures are amongst the highest in the world, with recent trends indicating a disturbing rise, especially amongst the younger age groups, across all races. Aim: This study analysed sociodemographic characteristics and trends relating to suicides committed in Durban, South Africa during the period of 2006-2007. Method: A retrospective analysis of suicidal deaths (during 2006-2007), extracted from autopsy registers at all three government-run mortuaries in Durban, was conducted. Results: The total number of suicides in Durban increased by 6.68% from 2006 to 2007. Suicide accounted for an average of 8.8% of all non-natural deaths per year of the study. The overall suicide rates of 14.53 (2006) and 15.53 (2007) per 100 000 population are comparable with national and global figures. The majority of suicides occurred in single unemployed persons, men and younger age groups. The largest number of suicides per year was recorded in black people, followed by Indian, white and mixed-race people. Hanging was the preferred method in the majority of victims, followed by self-poisoning, shooting and jumping. Conclusions: The findings indicate a disturbingly high suicide rate amongst the various population and age groups in Durban. The dominant methods used may be influenced by ease of access. The reported trends may worsen unless there is a swift and decisive public health response and cohesive community-based programmes which include a supportive multidisciplinary network.